2016
DOI: 10.1364/oe.24.004431
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the detection limits of infrared near-field microscopy regarding small buried structures and pushing them by exploiting superlens-related effects

Abstract: We present a study on subsurface imaging with an infrared scattering-type scanning near-field optical microscope (s-SNOM). The depth-limitation for the visibility of gold nanoparticles with a diameter of 50 nm under SiN is determined to about 50 nm. We first investigate spot size and signal strength concerning their particle-size dependence for a dielectric cover layer with positive permittivity. The experimental results are confirmed by model calculations and a comparison to TEM images. In the next step, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…24,30,91 ). The PZT film In contrast to far-field examinations, near-field measurements typically probe the sample volume up to a depth of about 100 nm, 33,96,97 resulting in negligible contributions of the STO substrate to the near-field signal of our 200-nm-thin PZT. 98 The near-field spectra of Figs.…”
Section: Z-cut Lithium Niobate (Lno)mentioning
confidence: 99%
“…24,30,91 ). The PZT film In contrast to far-field examinations, near-field measurements typically probe the sample volume up to a depth of about 100 nm, 33,96,97 resulting in negligible contributions of the STO substrate to the near-field signal of our 200-nm-thin PZT. 98 The near-field spectra of Figs.…”
Section: Z-cut Lithium Niobate (Lno)mentioning
confidence: 99%
“…cap on a nanoelectronic device), provided that the imaginary part of the cap material permittivity is sufficiently small. 182 To avoid the need for a near-field readout of the image from a superlens, there has been work on other classes of sub-diffraction-limited lenses which function by converting evanescent modes into propagating modes. In 2006, a so-called "far-field superlens" (FSL) was first developed which added a grating structure to a metallic film as in Fig.…”
Section: B Leveraging Superlensing and Near-field Optics For Imagingmentioning
confidence: 99%
“…Despite s-SNOM and nano-FTIR being surface scanning techniques, the finite penetration depth of near fields into the sample allows for subsurface probing of nanoscale structures and defects up to a depth of 100 nm [23][24][25][26][27] . For s-SNOM it has been also shown that depth-resolved information-with the potential of three-dimensional sample reconstruction-can be obtained by analysis of several higher harmonic signals, each of them having a different probing depth [28][29][30][31] .…”
mentioning
confidence: 99%